Minuman Tradisional Minangkabau Teh Talua (Teh Telur) Sebagai Objek Dalam Karya Serigaphy - Adinda Putri; Budiwirman Budiwirman (LPPM Politeknik Pratama, 2024)
This final work aims to introduce the traditional Minangkabau drink, teh talua (egg tea) into the form of graphic art by visualizing teh talua (egg tea) in graphic works using serigraphy techniques. There are several stages that are carried out in accordance with the method used in creating the work, namely: preparation, which is an observation related to the initial idea of the author's interest, elaboration is a stage to solidify the observation of information by collecting several references, journals, the internet or direct surveys will be very helpful in the elaboration stage related to the uniqueness of talua tea (egg tea) which must be cultivated, synthesis is the stage after getting the idea, what the author does next is to conclude and make an implementation schedule starting with preparation of the work until the creation of the work. The results created in the creation of graphic works of art are entitled